P-selectin deficiency promotes liver senescence in sickle cell disease mice - Vats, Ravi (Blood, 2021)
Sickle cell disease (SCD) is caused by a homozygous mutation in the β-globin gene, which leads to erythrocyte sickling, vasoocclusion, and intense hemolysis. P-selectin inhibition has been shown to prevent vasoocclusive events in patients with SCD; however, the chronic effect of P-selectin inhibition in SCD remains to be determined. Here, we used quantitative liver intravital microscopy in our recently generated P-selectin–deficient SCD mice to show that chronic P-selectin deficiency attenuates liver ischemia but fails to prevent hepatobiliary injury. Remarkably, we find that this failure in resolution of hepatobiliary injury in P-selectin–deficient SCD mice is associated with the increase in cellular senescence and reduced epithelial cell proliferation in the liver. These findings highlight the importance of investigating the long-term effects of chronic P-selectin inhibition therapy on liver pathophysiology in patients with SCD.